STRATEGI PEMASARAN PEDAGANG AYAM DI PASAR SINAR BERITA KECAMATAN PONTIANAK UTARA KOTA PONTIANAK: STRATEGI PEMASARAN PEDAGANG AYAM - rizka amanda (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2022)
the marketing strategy carried out by the traders in the news ray market, North Pontianak District, Pontianak City. The type of research used is descriptive research. The processed data is the result of interviews with traders and buyers in the market. The development and competition of the business world in the current era of globalization is getting higher. This study aims to determine the marketing strategy of chicken traders in the method used is qualitative based on observations, interviews, and documentation. The results showed that the marketing strategy carried out by basic food traders using several strategies, among others, product strategy, timeliness of opening and speed of serving buyers can have an effect on reducing income. Price strategy, price openness is needed in trading, so that the product khiyar (bargaining) process can be mutually beneficial promotional strategies, where merchants take an emotional approach to foster consumer trust, while at the same time fostering a high social spirit.